Economic Development in Seven Pacific Island Countries - Scott, Douglas (International Monetary Fund, 1989)
This book, by Christopher Browne with Douglas A. Scott, reviews the economic progress that Fiji, Kiribati, Papua New Guinea, Solomon Islands, Tonga, Vanuatu, and Western Samoa have made since independence. An overview of the region examines development strategies, external economic relations, the role of the private sector, and the evolution of financial structures. Seven country studies describe the main characteristics of each economy, analyze performance over the past decade, and provide detailed statistics suitable for cross-country comparison.